A Retrospective Study on Maternal Mortality in Rangpur Medical College Hospital - Ara, Mst Iffat; Soma, Shammi Akter; Hossain, Md Anowar; Khatun, Mst Safura (Journal of Rangpur Medical College, 2025)
Background: Bangladesh’s maternal mortality ratio (MMR: 156/100,000 live births, 2022), despite global declines, faces challenges from socioeconomic disparities, healthcare access gaps, and COVID-19. Despite national programs, achieving SDG-3 (MMR <70 by 2030) requires strengthened ANC, emergency obstetric services, and addressing systemic inequities. Objective: The study aimed to summarize the frequencies of sociodemographic characteristics, parity distribution, antenatal care patterns, and causes of death among maternal mortality. Methods: This retrospective study analysed maternal mortality at Rangpur Medical College Hospital, Bangladesh, in 2024, reviewing 4,741 birth records with 83 maternal deaths. Results: Among 83 maternal death, majority of deaths occurred among women aged 16–25 (41%) and those from low socioeconomic backgrounds (72.2%). Parity distribution showed 49.39% had 1–2 children, while 73.4% received no antenatal care (ANC), highlighting gaps in healthcare access. Eclampsia (37.35%) and obstetric hemorrhage (26.50%) were the predominant cause of death. Conclusion: The findings underscore persistent challenges in achieving Bangladesh’s SDG-3 target, particularly among socioeconomically disadvantaged and younger populations. Urgent priorities: strengthen ANC, emergency obstetric care, and address systemic inequities to improve healthcare infrastructure and reduce maternal mortality. J Rang Med Col. March 2025; Vol.10, No.1: 51-56